Comparison of mattress and continuous suturing techniques using polyglactin 910 and chromic catgut for episiotomy repair: an observational study - Mecheril Balachandran, Divya; Jacob, K. J.; Jayapalan Nair, Jayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: An episiotomy is an incision through the perineum to increase the vulvae outlet’s diameter and assist childbirth. Despite the fact that episiotomy is proven to benefit mothers, it is responsible for a significant percentage of both short-term and long-term postpartum morbidities. This study compares two different suture materials, namely polyglactin and chromic catgut, for episiotomy repair and short-term maternal morbidity. Methods: This was a prospective observational study conducted in the Department of Obstetrics and Gynaecology, Government Medical College, Thrissur. The data was collected and analysed using SPSS software. Results: A total of 400 participants who fulfilled the inclusion and exclusion criteria were studied. The majority of 214 women (53.5%) included in this study were between 20-25 years. 17(4.3%) women had edema (1 cm) at 24-48 hours after delivery. 43 (10.8%) women had more than 99-degree temperatures at 24-48 hours. 6 (1.5%) women had wound dehiscence at 6 weeks of them, 4 belonged to group 4. 98.3% had episiotomy wounds healed by primary intention. Conclusions: There was a reduction in wound dehiscence and more healing by primary intention in the polyglactin group than in the chromic catgut group. There was no significant reduction in short-term pain, temperature, induration and oedema between these groups. Hence, this study recommends a more rapidly absorbable form of polyglactin than traditional chromic catgut for perineal repair.